Applying foresight to policy agenda-setting: A successful case in South Korea. (March 2021) - Heo, Kyungmoo; Seo, Yongseok
Highlights: South Korea implemented a project in 2019 to proactively manage future conflicts by elevating future conflict issues to ongoing government institutional agendas. The project integrated agenda-setting strategies such as actor-based strategies, an issue-attention strategy, and packaging and utilized two-way translation methods of foresight. There are reasons for being successful - the nature of agenda-setting being conducive to foresight processes along with a leadership and active representation of future generations. A future conflict agenda-setting project can serve as a great entry point through which to increase the anticipatory knowledge and capacity of the actors involved. To internalize these, new anticipatory knowledge- and capacity-based governance should be introduced through training and education of both government officials and the public. Abstract: There is still a persistent gap between 'knowing' the future and implementing it in policymaking. South Korea implemented a project in 2019 to proactively manage future conflicts. The project was initiated to provide foresight-policymaking integration by elevating future conflict issues to ongoing government institutional agendas. Utilizing an exploratory, single-project case based on a field-study method, this article presents observations of the project's applied approaches in foresight-policy integration along with corresponding implications. The project integrated agenda-setting strategies such as actor-based strategies (inside-access, mobilization, and outside-initiation models), an issue-attention strategy, and packaging strategies (analogous to previous agendas and the utilization of symbols), as well as two-way translation methods of foresight (forecasting and backcasting). There are two underlying reasons for this integration being successful, namely the nature of agenda-setting being conducive to foresight processes and the project's key design variables (forward-looking leadership and the designated group's active representation of future generations). A future conflict agenda-setting project can serve as a great entry point through which to increase the anticipatory knowledge and capacity of the actors involved. To internalize these, however, new anticipatory knowledge- and capacity-based governance should be introduced through the continued training and education of both government officials and the public.